ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN MOBILE BANKING - Siagian, Kevin Adriel; Manzilati, Asfi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this study is to identify financial performance differences of Bank Negara Indonesia before and after the application of Mobile Banking. This research period is six years before (2010 – 2015) and six years after (2016 – 2021) implementation of Mobile Banking. Financial performance was analyzed from the aspects of capital (CAR), productive assets (NPL), profitability (ROA), efficiency cost (OER), and liquidity (LDR). Normality test showed that CAR and NPL was tested using Paired sample t-test. Meanwhile ROA, BOPO, and LDR were tested using Wilcoxon signed-rank test. SPSS 25 was used for data processing. This study finds that OER does not show difference in financial performance before and after application of Mobile Banking. In NPL, there’s a slightly decreased after Mobile Banking application, considered as insignificant. CAR and LDR indicate an increase in financial performance. ROA significantly decreased after the application, which caused by high cost of application development and short period of the research. This study recommends banking companies, particularly Bank Negara Indonesia, to promote activation of Mobile Banking. Furthermore, security issues are crucial for both public and banks. Implementing proactive cybersecurity, policy harmonization, and increasing people awareness concerning cyberattack can serve protection for both banks and customers.